2015
DOI: 10.1021/acs.nanolett.5b00869
|View full text |Cite
|
Sign up to set email alerts
|

Gbps Terahertz External Modulator Based on a Composite Metamaterial with a Double-Channel Heterostructure

Abstract: The past few decades have witnessed a substantial increase in terahertz (THz) research. Utilizing THz waves to transmit communication and imaging data has created a high demand for phase and amplitude modulation. However, current active THz devices, including modulators and switches, still cannot meet THz system demands. Double-channel heterostructures, an alternative semiconductor system, can support nanoscale two-dimensional electron gases (2DEGs) with high carrier concentration and mobility and provide a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(106 citation statements)
references
References 41 publications
1
105
0
Order By: Relevance
“…(a) and (b) used with permission from [179], (c) and (d) used with permission from [180], (e) and (f) used with permission from [178].…”
Section: Actively Switchable and Frequency Tunable Semiconductor Hybrmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) and (b) used with permission from [179], (c) and (d) used with permission from [180], (e) and (f) used with permission from [178].…”
Section: Actively Switchable and Frequency Tunable Semiconductor Hybrmentioning
confidence: 99%
“…Together with the causally connected phase modulation (up to 0.55 rad), this device allows broadband THz modulation [174] that can be used to replace a mechanical optical chopper in a lock-in THz detection scheme with modulation speed in the MHz range [176][177][178], limited either by the large device area accompanied with high stray capacitance or parasitic capacitance from the bonding electrodes and wires. Very recently, GHz electronic modulation speed has been demonstrated by using double-channel heterostructures supporting nanoscale 2DEGs with high carrier concentration and mobility [179], shown in figure 27(a). Through designing a composite hybrid metasurface structure to reduce the stray capacitance, 1 GHz modulation speed, 85% modulation depth (figure 27(b)), and a phase shift of 1.19 rad were experimentally realized during real-time dynamic tests.…”
Section: Page 39 Of 59mentioning
confidence: 99%
“…In Ref. [70], the authors demonstrated more than 1-GHz modulation speed (even though significant degradation was observed already above 200 MHz) and 86% modulation depth. In this work, InAlN/AlN/GaN/AlN/GaN double-channel heterostructures supported a 2DEG channel [68] and as a detector [13].…”
Section: Amplitude Modulatorsmentioning
confidence: 98%
“…Electronically tuneable 2DEG-based devices represent a parallel and viable route to achieving integrated amplitude modulators which yield excellent performances in high-speed modulation and modulation depths. Recent works targeted mostly the sub-THz frequency range [69,70], aiming at a direct monolithic integration of the modulators onto a chip with a view to a THz circuitry platform for communications. In Ref.…”
Section: Amplitude Modulatorsmentioning
confidence: 99%
“…Further development in plasmonic-based waveguides 88 could offer both low enough loss, field enhancement for interaction with a modulator or detection system and size reduction that are all desirable features in a future THz system. Further to such structures, the development in metamaterials can enable enhanced THz manipulation in devices 89 , in particular interesting work has been done on THz modulators using metamaterials 90,91 .…”
Section: Future Prospect and Challengesmentioning
confidence: 99%